Looking at the meaning of the word (Damascus University Journal of arts and humanities sciences, 2021)
This research is a study about a phenomenon that represents an unregular way of using the conjunction in Arabic, because it considers the meaning not the literal content as in usual, so that the two words that connected by a conjunction are not similar in their declension markers.Through this study we aim to reconsider some terms related to this phenomenon and its origin by looking at examples carried on it in the words of the earlier grammarians, and this rooting is useful in understanding their doctrines and how they analyze some traditional arabic expressions which were pointes of disagreements because some latest scholars has misunderstood their terms.It also reconsiders the conjunction that depends on illusion, and corrects some aspects related to it, as it clarifies that it is not specialized in poetic necessity but it can also be used in prose according to certain rules that the research attempted to investigate.
Keywords: Looking at the meaning of the word